Avaliação da gestão colegiada em uma maternidade de ensino em Fortaleza, na perspectiva dos gestores, colaboradores e usuários - Pinto, Maria Liduina Freitas (2019)
The changes taken place in health policies in recent years have proposed to health institutions, management models that allow the participation of all agents involved in the process of care as well as health. To actually enable the transformation, it is necessary to focus on training professionals who are going to work in such care and health care areas. With this thought in mind, the Ministry of Health dedicates to teaching hospitals the responsibility of training professionals in acccondance with the guidelines for humanization and health care, and suggests that changes in their working methods should use collegiate management as a tool. This study evaluates the collegiate management dynamics in a maternity school in Ceará, based on its managers, employees as well as employees and users’ point of view, highlighting path benefits and weaknesses. The development of this descriptive research, characterized as a case study, with a quantitative and qualitative approach to the problem, was carried out through the application of a questionnaire to the public referred to, and a survey of the manifestations accomplished by the users through the institution's ombudsman, in the year (2018), it was supported by the current legislation, institutional documents and contributions of researchers such as Campos (2018a), Santos Filho (2009), Cecílio (2010), among others. The main conclusions point to the fact that, among managers and employees, the main objective of collegiate management is team work and valorization which favor democratization and collective decision-making, joint responsibility and sharing of problems and solutions, besides establishing priorities and achieveing greater assertiveness in deliberative processes. The research also revealed that the greatest benefit of collegial management, in the view of the subjects, is knowledge and sharing of problems in the unit / institution, integration between professional categories and knowledge exchange. The results also revealed evident weaknesses, such as lack of knowledge of the professionals about the existence of collegiate management in the maternity-school referred to, low diversity among those attending the collegiate meeting, few demonstrations of users included in the collegiate meeting guidelines and the need for training of their actors.